Vulnerabilidade de aquíferos cársticos com cobertura espessa de solo: metodologia COP-Solo em ambiente tropical úmido - Rogério Tadeu de Souza (2020)
Karstic areas play an important role in providing drinking water worldwide. Several European countries are exclusively supplied with water from karst aquifers. Therefore, there is a constant concern to protect the quality of these waters. Diverse methods of contamination vulnerability have been proposed for aquifer protection, but few are aplicable to karst. The COP method, acronym used to designate the parameters C=Concentration flow, O=Overlaying layers, and P=Precipitation, was developed for the protection of karst aquifers in Mediterranean European countries and showed decent results. However, its direct application in the tropical karst must be modified, mainly because there is extreme difference in the layer that protects the aquifer (O Factor). Thus, this thesis sought to modify the original method by applying the characteristics of the soil in the vadose zone with the creation of the COP-Soil method in part of the one of the most studied karstic areas of Brazil, the EPA Carste Lagoa Santa (Environmental Protection Area Lagoa Santa Karst). The application of the COP method requires high level of qualitative and quantitative information. The original project area covered a total area of 504 km2. Due to scarcity of data, the research area has been reduced to 240 km2, to maintain a satisfactory level of reliability. In order to adapt the O Factor and creation of the COP-Soil method, a natural attenuation index has been created taking into account the intrinsic characteristics of the soil layer that protects the tropical karstic aquifer (thickness, mineralogy, CEC, hydraulic conductivity, OC, pH and percentage of clay) which is completely different from the soil layer that protects the European karst aquifer. The results presented found modifications to be necessary. The COP-Soil method applied to the study area (240 km2) showed more refined and different vulnerability results. As expected, the very low (64,88%) and low (28,55%) were predominant in the original methodology due to soil ticknesses being greater than one meter. In the modified methodology the dominant classes were moderate (44,29%), followed by the lower class (38,19%). The very high (5,93%) and high (11,30%) classes were detected with made more evident by the COP-Soil methodology. The results indicate that the original methodology needs to be modified for application in humid tropical karst with significant soil cover.